2017
DOI: 10.1080/19325037.2016.1271755
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sun Protection at Outdoor Recreation and Leisure Venues at Resorts in North America

Abstract: Background Exposure to solar ultra violet radiation (UVR) is a primary risk factor for skin cancer. Vacationers often fail to protect themselves from harmful UVR. Purpose The study assessed the sun protection practices of resort guests in various outdoor leisure and recreation venues during warm-weather seasons. Method 41 North American resorts were enrolled in a quasi-experimental randomized controlled trial. Adult guests were observed (n=4091) and surveyed (n=3694) in a cross sectional sample. Data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…The lower sun protection observed among males and adolescents in the present study is consistent with findings from self-report and direct observation surveys conducted both in Australia (Dixon et al, 2008; Dobbinson, Wakefield, Hill, et al, 2008; Makin et al, 2013; Volkov et al, 2013) and internationally (Buller et al, 2011; Kasparian et al, 2009; Pinault & Fioletov, 2017; Walkosz et al, 2017). It is unlikely that males and adolescents’ inferior use of physical sun protection would be offset by extensive use of sunscreen.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lower sun protection observed among males and adolescents in the present study is consistent with findings from self-report and direct observation surveys conducted both in Australia (Dixon et al, 2008; Dobbinson, Wakefield, Hill, et al, 2008; Makin et al, 2013; Volkov et al, 2013) and internationally (Buller et al, 2011; Kasparian et al, 2009; Pinault & Fioletov, 2017; Walkosz et al, 2017). It is unlikely that males and adolescents’ inferior use of physical sun protection would be offset by extensive use of sunscreen.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrates differences in the prevalence and observed forms of sun protection used in public outdoor settings and variation by demographic and activity characteristics and weather conditions. Clothing covering at least 3/4 of the arms and/or legs was less commonly worn at pools/beaches relative to streets/cafes and parks/gardens, while shade was more commonly used at streets/cafes, in line with previous observations in outdoor dining areas, pools and beaches at North American holiday resorts (Walkosz et al, 2017). In the present study, there were some commonalities across settings, including that females and older adults were better protected than males and adolescents respectively, but sun protection (especially covering hat use and arm cover) was largely inadequate.…”
Section: Discussionsupporting
confidence: 85%
“…Yet, if the type of physical activity is organized sports, the prevalence of sunscreen use is lower [7,8,23]. Sun avoidance behaviors, such as seeking shade or not going outdoors, is negatively related with leisure-time activity, such as in resorts or at beaches [24,25]. Similarly, we found that longer duration leisure walking was negatively associated with sun avoidance.…”
Section: Discussionmentioning
confidence: 72%
“…A different approach may be multicomponent community-wide interventions, which combine individual-level intervention with community or policy supports [43] or modifications of environments to facilitate sun protection. A review of environmental and policy interventions to promote sun protective behaviors in recreation and tourism settings have mixed results [44] and the provision of shade at vacation destinations may not be utilized by vacationers [25]. Some modifications of the built environment, such as bus stop shelters, store front canopies, or street trees, may provide some sun protection for transportation walking [45].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, since the amount of time people spent at recreational settings is increasing among Western populations [75,76]. The amount of UVR exposure at these venues is often high [21] while sun protection is regularly lacking during outdoor activities [77][78][79] and no prevention policies are at place. Moreover, children specifically are at high risk of receiving large amounts of UVR at playgrounds due to unavailability of shaded areas, as revealed by a recent study conducted in Germany [80].…”
Section: Discussionmentioning
confidence: 99%